Bibliometric Analysis of Neuroinflammation and Postoperative Cognitive Dysfunction - Zheping Chen; Zhenxiang Zuo; Yizheng Zhang; Guoliang Shan; Le Zhang; Moxuan Gong; Yuyang Ye; Yufeng Ma; Yanwu Jin (Brain and Behavior)
ABSTRACT Background The occurrence and development of postoperative cognitive dysfunction (POCD) are closely linked to neuroinflammation. This bibliometric analysis aims to provide novel insights into the research trajectory, key research topics, and potential future development trends in the field of neuroinflammation‐induced POCD. Methods The Web of Science Core Collection (WoSCC) database was searched to identify publications from 2012 to 2023 on neuroinflammation‐induced POCD. Bibliometric analysis, involving both statistical and visual analyses, was conducted using CiteSpace, VOSviewer, and the R software. Results Research on neuroinflammation‐induced POCD has exhibited an increasing trend over the past 12 years. China had the highest number of publications, Nanjing Medical University had the most collaboration with other institutions, Zhiyi Zuo was the most published author, and the Journal of Neuroinflammation served as the primary publication in the field of neuroinflammation‐induced POCD. The most frequent keyword was POCD. Keyword clustering analysis indicated that the predominant cluster is dexmedetomidine. Burst detection revealed that postoperative delirium (POD), perioperative neurocognitive disorders (PND), apoptosis, and epigenetic modifications were the future research trends. Conclusions Our analysis identified the following key research areas associated with neuroinflammation‐induced POCD: anesthesia, surgery, dexmedetomidine, NLRP3 inflammasome, and mechanism of neuroinflammation‐induced POCD. The potential future research topics comprise POD, PND, apoptosis, and epigenetic modifications.